Cochlear implants and other implantable hearing devices - Ruckenstein, Michael J.; Ruckenstein, Michael J. (San Diego c)
"Cochlear Implants and Other Implantable Hearing Devices, Second Edition remains a fundamental text for hearing professionals. Cochlear implants and other implantable hearing mechanisms have become increasingly prevalent solutions to modern-day hearing trauma, making it imperative for clinicians to gain expertise on the subject. This text provides hearing professionals with the knowledge necessary to wholly understand these implantable mechanisms so that they can incorporate them into their practices"--
Keywords: Audiology